2011
DOI: 10.1007/s13410-011-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic etiology of type 2 diabetes mellitus: a review

Abstract: Type 2 diabetes mellitus (T2DM) is the most common form of diabetes characterized by elevated levels of plasma glucose caused by impairment in both insulin secretion and action. It is becoming an epidemic leading to various complications and its prevalence and incidence are increasing at an alarming rate in developing countries like India, raising a major public health concern. Both the genetic and environmental factors play a strong role in the manifestation of this complex genetic disorder. In the recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 130 publications
0
27
0
Order By: Relevance
“…Several genomewide association studies (GWASs) have implicated ZnT8 in T2DM in humans [8, 155157]. Thus, having two copies of the at-risk polymorphic variant rs13266634, a nonsynonymous single nucleotide polymorphism (SNP) (Arg325Trp) in ZnT8 is associated with a 43% increase risk of developing diabetes [158].…”
Section: Modes Of Zinc Signaling Zinc Transporters and Insulin Smentioning
confidence: 99%
See 1 more Smart Citation
“…Several genomewide association studies (GWASs) have implicated ZnT8 in T2DM in humans [8, 155157]. Thus, having two copies of the at-risk polymorphic variant rs13266634, a nonsynonymous single nucleotide polymorphism (SNP) (Arg325Trp) in ZnT8 is associated with a 43% increase risk of developing diabetes [158].…”
Section: Modes Of Zinc Signaling Zinc Transporters and Insulin Smentioning
confidence: 99%
“…The prevalence of this metabolic disorder is expected to increase from 171 million people in 2000 to 366 million in 2030, predominately due to changes in nutrition, reduced physical activity, and obesity [4]. Complications arising from T2DM include renal failure [5], blindness [6], and dyslipidemia [7], and it is widely accepted to be a fundamental and foremost basis for cardiovascular disease [8]. Given this projection, T2DM is becoming a leading cause of morbidity and mortality that results in a significant reduction in quality of life and life expectancy [9].…”
Section: Introductionmentioning
confidence: 99%
“…The different types of diabetes include types 1 and 2 in addition to rare forms of the disease such as gestational diabetes and maturity onset diabetes in youth (MODY) (Kommoju and Reddy, 2011). Type 2 diabetes (T2D) is the most common form of the disease, accounting for approximately 90% of the diabetes cases worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that the intake of calcium contributes to maintaining healthy blood glucose levels. The role of genetic factors in the development of diabetes is universally known (37). Therefore, for some people with normal blood glucose and family history of diabetes, we consider that calcium supplementation may appropriately reduce their risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%